A distinctive new species of the genus Polyonyx Stimpson, 1858 (Crustacea: Decapoda: Anomura: Porcellanidae) from Okinawa, southwestern Japan - Osawa, Masayuki; Sato, Taigi (Zootaxa, 2022)
The new porcellanid crab Polyonyx deezi n. sp. is described on the basis of two specimens from Okinawa Island, Ryukyu Islands, southwestern Japan. The new species belongs to the P. sinensis group and may be closest to P. socialis Werding & Hiller, 2019 in the comparatively broad proportions of the carpi of the chelipeds and meri of the ambulatory legs. However, P. deezi n. sp. is immediately distinguished from all other congeners by the median branchial margins of the carapace being bluntly angular and produced laterally and the dorsal surfaces of the carapace and chelipeds with distinct protuberances. The occurrence of P. deezi n. sp. from coral reefs may be unusual in species of the P. sinensis group because many of the known species have been recorded from estuaries or coastal embayments. An identification key to the Indo-West Pacific species of the Polyonyx sinensis group is provided.